Altered thermogenesis and impaired bone remodeling in Misty mice - Motyl, Katherine J (2013)
Fat mass may be modulated by the number of brown-like adipocytes in white adipose tissue (WAT) in humans and rodents. Bone remodeling is dependent on systemic energy metabolism and, with age, bone remodeling becomes uncoupled and brown adipose tissue (BAT) function declines. To test the interaction between BAT and bone, we employed Misty (m/m) mice, which were reported be deficient in BAT. We found that Misty mice have accelerated age-related trabecular bone loss and impaired brown fat function (including reduced temperature, lower expression of Pgc1a and less sympathetic innervation compared to wildtype (+/+)). Despite reduced BAT function, Misty mice had normal core body temperature, suggesting heat is produced from other sources. Indeed, upon acute cold exposure (4°C for 6 hr), inguinal WAT from Misty mice compensated for BAT dysfunction by increasing expression of Acadl, Pgc1a, Dio2 and other thermogenic genes. Interestingly, acute cold exposure also decreased Runx2 and increased Rankl expression in Misty bone, but only Runx2 was decreased in wildtype. Browning of WAT is under the control of the sympathetic nervous system (SNS) and, if present at room temperature, could impact bone metabolism. To test whether SNS activity could be responsible for accelerated trabecular bone loss, we treated wildtype and Misty mice with the β-blocker, propranolol. As predicted, propranolol slowed trabecular BV/TV loss in the distal femur of Misty mice without affecting wildtype. Finally, the Misty mutation (a truncation of DOCK7) also has a significant cell-autonomous role. We found DOCK7 expression in whole bone and osteoblasts. Primary osteoblast differentiation from Misty calvaria was impaired, demonstrating a novel role for DOCK7 in bone remodeling. Despite the multifaceted effects of the Misty mutation, we have shown that impaired brown fat function leads to altered SNS activity and bone loss, and for the first time that cold exposure negatively affects bone remodeling.